The extent of factors influencing automobile salesperson’s career tenure in Malaysia - Zain, Osman M.; Jan, Muhammad Tahir (Asia Business Research Corporation (ABRC) Limited, 2014)
Salesperson’s tenure is a major issue for companies especially in today’s era of high competition. A high rate of employee turnover is reported to impact organizational productivity and competitiveness. The present study aims to identify and test those factors which play an important role in salesperson’s career tenure. For this purpose, data was collected from 400 sales personnel, working in various automobile companies, through self-administered questionnaire. The data analysis was conducted using SPSS and AMOS software. Factor analysis was performed to extract and decide on the number of factors underlying the measured variables of interest. Structural equation modelling (SEM) was then used to examine the variables and the fitness of proposed model. We found a significant positive impact of intrinsic motivation on job satisfaction and organizational commitment. Similarly, we also found the impact of organizational commitment on employee productivity and tenure. The findings of this study have a major implication for marketing organizations and more specifically for recruitment agencies.